Pre-operative diagnosis of hydatid cyst in the breast: A case report of a rare entity and review of literature - Mahmood, Sidrah; Mahmood, Rabiaa (Journal of the Pakistan Medical Association, 2023)
Hydatid cysts are mainly found in the liver and lungs. Only few cases have been reported in the breast and majority of these cases have been diagnosed post-operatively. We report a case of hydatid cyst of the breast diagnosed pre-operatively by fine needle aspiration and cytology (FNAC), without any complication. A 50 years old female presented with a slowly growing mobile lump in the left breast for 3 years. Mammography showed a circumscribed opacity in left breast. High resolution ultrasound displayed a unilocular cyst with some echogenic specks settling to the gravity dependent portion. An aspiration was planned and, as the cyst volume decreased, membranes appeared within the residual fluid and started settling down. Cytology of aspirated fluid revealed a hydatid cyst. Hydatid cysts in the breast are rare but possible, particularly in endemic regions. —Continue